Brand Equity of A Tourist Destination: An Analysis of Domestic Tourists' Perspectives - Chairunnisya Chairunnisya; Hapsari Setyowardhani (AMAR (Andalas Management Review), 2021)
According to the Ministry of Tourism's performance in 2019, an increase in international tourist visits to 16.1 million persons resulted in a Rp 280 trillion increase in foreign exchange earnings. This industry currently provides 5.5 % to the national gross domestic product and is expected to grow to 9.9 % by 2025. The purpose of this study is to ascertain tourist behavior by evaluating the application of the Bukittinggi City Brand Equity as a tourist destination from the perspective of domestic tourists who have visited the Bukittinggi City and identifying the Brand Equity dimensions, namely brand awareness, brand loyalty, perceived quality, and brand image. This study employs a quantitative methodology. Explanatory studies utilizing hypothesis testing and descriptive analysis are the types of study. The data for this study came from an online survey of 150 domestic visitors that visited Bukittinggi. A one-sample T-test and mean ranking are used to determine how each dimension of Brand Equity is formed. The One-Sample T-Test revealed that the four dimensions had an effect on the behavior of tourists in Bukittinggi City.